FERRUM ION RELEASE AND STIFFNESS CHANGES OF STAINLESS STEEL ORTHODONTIC WIRE IMMERSED IN DIFFERENT CONCENTRATIONS OF PIPER BETLE LINN MOUTHWASH - DERIATY, TANTI; BAHIRRAH, SITI; ANGELIA, VERONICA; FITRI, ATIKA RESTI; MANURUNG, CLARA NATASYA; SITORUS, IMA THRESIA PUTRI (International Journal of Applied Pharmaceutics, 2025)
Objective: Successful orthodontic treatment is related to patient oral hygiene. Using mouthwash is one way to maintain good oral hygiene. Orthodontic archwire that placed in oral cavity has contact with all components in mouth, including chemical mouthwash that using by the patient. This leading to a corrosion process that would affected the mechanical properties of the arch wire. Herbal mouthwash become an alternative to maintain patient’s oral hygiene. This study was to examined ferrum ion release and stiffness value of stainless steel orthodontic wire immerse in artificial saliva, 0.2% chlorhexidine, and 1%, 2%, and 3% Piper betle Linn mouthwash. Methods: Seventy-five stainless steel orthodontic wires were immersed in artificial saliva, 0.2% chlorhexidine, and 1%, 2%, 3% Piper betle Linn mouthwash. Each wire was inserted into a polypropylene tube containing 10 ml solution then placed in an incubator at 37 °C for 1,7 and 14 d. The solution was used to measure ferrum ion release by ICP-OES, and the wire was dried to test the stiffness values by a Universal Testing Machine. Results: There was a significant increase in ferrum ion release and a significant decrease in stiffness in all immersion groups. The results has significant differences between groups (p<0.05). Conclusion: The lowest ferrum ion release and the highest stiffness value between Piper betle Linn mouthwash were found in 3% Piper betle Linn mouthwash. It because there is more tannin content in 3% Piper betle Linn mouthwash than 1% and 2% Piper betle Linn mouthwash.